PENGEMBANGAN INDIKATOR 4 C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMP/MTs KELAS VIII SEMESTER 2 - Setiyawati, Endah Dwi; Sunardi, Sunardi; Kurniati, Dian (Kadikma, 2017)
Abstract. This research aims to describe process and development result of 4 C’s indicators that in accordance with curriculum 2013 on the second semester mathematics subject of eighth grade junior high school. The 4 C's indicators is the basic skill that students needed in the 21st century to. According to P21, 4 C’s abilities are critical thinking, creative, collaboration and communication. eighth grade be able to compete in the global community material on the second semester consists of 5 chapters(1) Pythagorean theorem, (2) t circle, (3) flat face three dimentional object, (4) statistics, and (5) opportunities. Research type which is used in modified Plomp's development model consists of 4 phase which are, (1) initial investigation phase; (2) designing phase; (3) realisation/construction phase; (4) test, evaluation, and revision phase. The implementation phase is not used in this research. The data collection process is done through product validity test which has been developed by several lecturers and teachers. Validation result of this 4 C’s indicators development has 3,876 Therefore, it can be concluded the development 4 C’S indicators that in accordance with with 2013 curriculum on the second semester mathematics subject of eighth grade junior high school has been qualified valid criterion. Keyword: Plomp's development model, 4 C's indicators, Curriculum 2013.